1988
DOI: 10.1021/np50055a009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Benzoxazinoids from Roots of Coix lachryma-jobi var. Ma-yuen

Abstract: The anti-inflammatory activities of six benzoxazinoids isolated from roots of Coix lachryma-jobi var. ma-yuen and structurally related synthetic materials were investigated by measurement of their inhibition of histamine release from rat mast cells stimulated with concanavalin A (Con A) and sensitized with immunoglobulin E (reagin). Because the inhibition data for either Con A or IgE with these compounds were comparable, Con A can be used for rapid first-stage screening of active compounds. Four glycosides out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 14 publications
(18 reference statements)
2
62
0
2
Order By: Relevance
“…The HMBC correlations of compound 5. 9) and phenylpropanoids (14-15) as the major constituents are in agreement with Thai traditional usage as an anti-inflammatory preparation (Otsuka et al, 1988;Cometa et al, 1993). Furthermore, the toxicological and pharmacological properties of benzoxazinoids have been reported as the chemical resistance factors against insects, fungi, bacteria and viruses in many crop plants of the family Gramineae (Niemeyer, 1988;Sicker et al, 2000), as well as having mutagenic activities (Hashimoto and Shudo, 1996).…”
Section: Resultssupporting
confidence: 65%
“…The HMBC correlations of compound 5. 9) and phenylpropanoids (14-15) as the major constituents are in agreement with Thai traditional usage as an anti-inflammatory preparation (Otsuka et al, 1988;Cometa et al, 1993). Furthermore, the toxicological and pharmacological properties of benzoxazinoids have been reported as the chemical resistance factors against insects, fungi, bacteria and viruses in many crop plants of the family Gramineae (Niemeyer, 1988;Sicker et al, 2000), as well as having mutagenic activities (Hashimoto and Shudo, 1996).…”
Section: Resultssupporting
confidence: 65%
“…It has been reported that AHM possesses some low-molecular-weight and moderately polar substances that have antioxidative effects (23). Moreover, at least of the following six classes of chemical constituents of AHM have been demonstrated: lignan, phenolic acid, phytosterols, polyphenols, polysaccharides, and flavonoids (15,22,34,43). In our previous study (15), we quantified the components of the AHM-EA fraction; it contained naringenin, quercetin, vanillin, syringaldehyde, gallic acid, syringic acid, and p-coumaric acid.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Some active compounds previously isolated from the adlay seed include coixenolides that possess anti-tumor effects, 13) coixans A, B, and C that possess hypoglycemic effects, 14) and benzoxazinones that possess anti-inflammatory effects. 15) In our search for novel PPARg agonists, we selected 88 herbal crude drugs that are frequently used in Kampo medicines. Compounds isolated from the adlay seed extract showed relatively high PPARg agonist activity and the structures of the active compounds were determined to be hydroxy unsaturated fatty acids.…”
mentioning
confidence: 99%